Parental Feeding Practices and Nutritional Status Among Preschool Children in Urban Indonesia: Implications for Family-Centered Nursing - Widia Sari; Erna Veronika; Kartini Kartini; Rian Adi Pamungkas (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: Parental feeding practices significantly influence children’s eating habits and growth. In Indonesian urban settings, shifting diets and lifestyles have created a double burden of malnutrition. This study examined the relationship between parental feeding practices and the nutritional status of preschool children in West Jakarta, Indonesia. Methods: A cross-sectional survey was conducted among 255 caregiver–child pairs (children aged 3-6 years) recruited from early childhood education centres in West Jakarta. Caregivers completed the Indonesian-adapted Child Feeding Questionnaire (CFQ), which classified feeding approaches as responsive or non-responsive. Children’s weight and height were measured, and nutritional status classified using WHO growth standards. Descriptive statistics were applied, followed by chi-square tests to examine associations between feeding practices and sociodemographic characteristics. Spearman’s rank correlation assessed the relationship between feeding practices and nutritional status. Multivariable multinomial logistic regression estimated adjusted associations controlling for maternal education, household income, recent illness, and participation in growth and development screening. Results: Among caregivers, 143 (56.1%) reported responsive feeding, while 112 (43.9%) used non-responsive feeding. Higher maternal education and household income were significantly associated with responsive feeding (p < 0.05), whereas recent illness was associated with non-responsive feeding. Feeding practices showed a weak but significant correlation with nutritional status (r = 0.123; 95% CI: 0.001-0.242 p = 0.04), explaining 1.5% of the variance. However, after adjustment, feeding practices were not independently associated with nutritional status. Recent illness increased the odds of undernutrition (aOR = 3.16; 95% CI: 1.61-6.21), while participation in growth and development screening demonstrated protective associations against undernutrition and overnutrition. Conclusion: Responsive feeding showed a modest association with nutritional status in bivariate analysis, while child health status and preventive service engagement emerged as stronger independent correlates. Integrating responsive feeding education into pediatric and community nursing practice may support family-centered strategies addressing determinants of child nutrition in urban settings.